Understanding fandom : an introduction to the study of media fan culture - Duffett, Mark. (New York : Bloomsbury, 2013)
"While fans used to be seen as an overly obsessed fringe audience, shifts in technology and production in the last few decades have made fandom a central mode of media consumption. An abundance of theorists have emerged in parallel to explore this phenomenon, many specializing in particular kinds of fan research. Although the volume will not address sports fandom, it will aim to include insights from research linked to many other kinds of media, including television and popular music fandom. With a foreword by Matt Hills, Understanding Fandom introduces the whole field of fan studies by looking at the history of debate, key paradigms and methodogical issues. The emphasis will be on showing how fan studies is an emergent interdisciplinary field with its own key scholars and a tradition that is distinct from both textual analysis and reception studies. It draws together a range of debates from media studies, cultural studies and psychology to argue that fandom is particular kind of an engagement with the power relations of media culture"--
Foreword: What if?: reimagining fandom / Matt Hills -- 1. Introduction -- 2. Fan stereotypes and representations -- 3. Beyond the text -- 4. The pathological tradition -- 5. How do people become fans? -- 6. Fan practices -- 7. Fandom, gender and sexual orientation -- 8. Myths, cults and places -- 9. The ran community: Online and Offline -- 10. Researching random -- 11. Conclusion: The frontiers of fan research.
Includes bibliographical references (pages 311-330) and index.
Keywords: Fans (Persons); Mass media -- Social aspects; Mass media and culture; Fans (Persons); Mass media and culture; Mass media -- Social aspects